Pengembangan Multimedia Interaktif Sebagai Sumber Belajar Inovatif Untuk Mengembangkan Kemampuan Kognitif Pada AUD Usia 5-6 Tahun - Sinurat, Uli Artha Aprilia; Tanjung, Samsidar; Endriani, Dewi (Jurnal Ilmiah Global Education, 2025)
This research and development study aims to produce PowerPoint-based interactive multimedia that is valid, practical, and effective in improving the cognitive abilities of early childhood aged 5-6 years on the theme of Land Vehicles. This study employs the ADDIE development model, which consists of five stages: (1) Analyze stage to assess the needs of teachers, students, and curriculum, (2) Design stage to develop an interactive learning media prototype, (3) Development stage to create and validate the media with experts, (4) Implementation stage to conduct trials with students, and (5) Evaluation stage to assess and refine the quality of the learning media. The research findings indicate that: (1) Validation by subject matter experts resulted in an average score of 95%, categorized as highly valid. (2) Validation by instructional design experts achieved an average score of 94.33%, categorized as highly valid. (3) Validation by media experts obtained an average score of 86.66%, categorized as highly valid. (4) Individual trials resulted in an average score of 95.14%, categorized as highly valid. (5) Small group trials resulted in an average score of 95%, categorized as highly valid. (6) Field trials resulted in an average score of 92.92%, categorized as highly valid. The effectiveness test showed that the experimental class using interactive multimedia obtained an average post-test score of 64.1, whereas the control class using printed books scored an average of 57.5. The independent t-test results showed that tcalculated > ttable (7.788 > 2.12), indicating a significant difference between the experimental and control classes. Therefore, the developed PowerPoint-based interactive multimedia has been proven to be effective in enhancing early childhood cognitive abilities.